Integration of Deepfake Technology in Promotional Videos to Enhance MSME Economic Utility in Bireuen Regency - Heri Gustami; Deni Sumantri; Najmuddin Najmuddin (Universitas Budi Darma, 2026)
This study examines the integration of deepfake technology in UMKM promotional practices by focusing on its strategic value, ethical dimensions, implementation risks, and economic utility. A qualitative approach with a naturalistic phenomenological design was employed to explore the experiences, perceptions, and readiness of UMKM actors, promotion teams, and consumers in using deepfake-based promotional content. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña with NVivo support. The findings indicate that deepfake is perceived as a promising promotional innovation because it can enhance visual appeal, extend promotional reach, and improve cost and time efficiency in content production. However, its adoption is shaped by important constraints, particularly content authenticity, ethical considerations, audience response, human resource capacity, and the risk of misleading consumers. The study also shows that the economic utility of deepfake in UMKM promotion is meaningful only when promotional efficiency is balanced with ethical control, digital literacy, and consumer trust. These findings suggest that deepfake adoption in UMKM should not be understood merely as a technological issue, but as a negotiation between economic value, digital capability, reputational risk, and moral legitimacy.Abstract is a brief summary of the paper to help readers quickly determine the main research problem, solutions to solving problems encountered, research objectives and temporary research results which can be in the form of numbers/percentages according to research needs. Abstract should be clear and informative, providing a statement for the problem under study and its solution. Abstract length between 90 to 230 words. Avoid unusual abbreviations and define all symbols used in the abstract. Using keywords related to the research topic is recommended.